Prognostic scoring systems for myelodysplastic syndromes (MDS) in a population‐based setting: a report from the Swedish MDS register. (29th April 2018) - Moreno Berggren, Daniel; Folkvaljon, Yasin; Engvall, Marie; Sundberg, Johan; Lambe, Mats; Antunovic, Petar; Garelius, Hege; Lorenz, Fryderyk; Nilsson, Lars; Rasmussen, Bengt; Lehmann, Sören; Hellström‐Lindberg, Eva; et al.
Summary: The myelodysplastic syndromes (MDS) have highly variable outcomes and prognostic scoring systems are important tools for risk assessment and to guide therapeutic decisions. However, few population‐based studies have compared the value of the different scoring systems. With data from the nationwide Swedish population‐based MDS register we validated the International Prognostic Scoring System (IPSS), revised IPSS (IPSS‐R) and the World Health Organization (WHO) Classification‐based Prognostic Scoring System (WPSS). We also present population‐based data on incidence, clinical characteristics including detailed cytogenetics and outcome from the register. The study encompassed 1329 patients reported to the register between 2009 and 2013, 14% of these had therapy‐related MDS (t‐MDS). Based on the MDS register, the yearly crude incidence of MDS in Sweden was 2·9 per 100 000 inhabitants. IPSS‐R had a significantly better prognostic power than IPSS ( P  < 0·001). There was a trend for better prognostic power of IPSS‐R compared to WPSS ( P  = 0·05) and for WPSS compared to IPSS ( P  = 0·07). IPSS‐R was superior to both IPSS and WPSS for patients aged ≤70 years. Patients with t‐MDS had a worse outcome compared to de novo MDS (d‐MDS), however, the validity of the prognostic scoring systems was comparable for d‐MDS and t‐MDS. In conclusion, population‐based studies are important to validate prognostic scores in a 'real‐world' setting. In our nationwide cohort, the IPSS‐R showed the best predictive power.